Family and Psychosocial Functioning in Bipolar Disorder: The Mediating Effects of Social Support, Resilience and Suicidal Ideation - Dou, Wenbo; Yu, Xueying; Fang, Hengying; Lu, Dali; Cai, Lirong; Zhu, Caihong; Zong, Kunlun; Zheng, Yingjun; Lin, Xiaoling (Frontiers in Psychology, 2022)
Patients with bipolar disorder (BD) may experience family dysfunction, which might result in worse psychosocial functioning through environmental and psychological factors. Research investigating the mediating role of social support, resilience and suicidal ideation on family and psychosocial functioning in BD is rare. The study aims to explore the predicting and mediating effects of social support, resilience and suicidal ideation on family and psychosocial functioning in BD patients. Two hundred forty-six patients with BD and sixty-nine healthy controls were recruited. The Family Assessment Device (FAD), Functioning Assessment Short Test (FAST), Social Support Rating Scale (SSRS), Connor-Davidson Resilience Scale (CD-RISC) and Beck Scale for Suicide Ideation (BSI) were used to assess family functioning, psychosocial functioning, social support, resilience and suicidal ideation, respectively. Bipolar patients exhibited worse family and psychosocial functioning than healthy controls. Family functioning, social support, resilience and suicidal ideation significantly predict psychosocial functioning in the bipolar group. Social support, resilience and suicidal ideation indirectly mediate the effect of family functioning on psychosocial functioning in bipolar patients. Cross-sectional design and mixed sample including acute and remitted stages. Treatments for patients with bipolar disorder should be combined with family strategies that are formulated to improve psychosocial functioning. An emphasis should be placed on enhancing social support and resilience while paying attention to suicidal ideation.